Novel methods to characterise spatial distribution and enantiomeric composition of usnic acids in four Icelandic lichens. (August 2022) - Xu, Maonian; Oppong-Danquah, Ernest; Wang, Xiaoyu; Oddsson, Sebastian; Abdelrahman, Asmaa; Pedersen, Simon Vilms; Szomek, Maria; Gylfason, Aron Elvar; Snorradottir, Bergthora Sigridur; Christensen, Eva Arnspang; Tasdemir, Deniz; Jameson, Cynthia J.; et al.
Abstract: Usnic acid is an antibiotic metabolite produced by a wide variety of lichenized fungal lineages. The enantiomers of usnic acid have been shown to display contrasting bioactivities, and hence it is important to determine their spatial distribution, amounts and enantiomeric ratios in lichens to understand their roles in nature and grasp their pharmaceutical potential. The overall aim of the study was to characterise the spatial distribution of the predominant usnic acid enantiomer in lichens by combining spatial imaging and chiral chromatography. Specifically, separation and quantification of usnic acid enantiomers in four common lichens in Iceland was performed using a validated chiral chromatographic method. Molecular dynamics simulation was carried out to rationalize the chiral separation mechanism. Spatial distribution of usnic acid in the lichen thallus cross-sections were analysed using Desorption Electrospray Ionization-Imaging Mass Spectrometry (DESI-IMS) and fluorescence microscopy. DESI-IMS confirmed usnic acid as a cortical compound, and revealed that usnic acid can be more concentrated around the algal vicinity. Fluorescence microscopy complemented DESI-IMS by providing more detailed distribution information. By combining results from spatial imaging and chiral separation, we were able to visualize the distribution of the predominant usnic acid enantiomer in lichen cross-sections: (+)-usnic acid in Cladonia arbuscula and Ramalina siliquosa, and (−)-usnic acid in Alectoria ochroleuca and Flavocetraria nivalis . This study provides an analytical foundation for future environmental and functional studies of usnic acid enantiomers in lichens. Graphical abstract: Image 1 Highlights: A chiral HPLC method was validated to determine usnic acid (UA) enantiomer ratios. Molecular dynamics simulation revealed chiral chromatographic mechanisms. MS imaging was used for spatial distribution of UA in lichen cross sections. Fluorescence microscopy was used for spatial imaging of UA in lichen cross sections.